Variação genética e desempenho de progênies de Pinus caribaea var. hondurensis para produção de madeira e resina - Santos, Wanderley dos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Pinus caribea var. hondurensis is a species of the genus Pinus which is very important to tropical regions. Its wood and resin are used in various niches of the forest sector. However, the supply of quality genetic seeds are produced by few private companies and public institutions, especially by those in the resin sector. The aim is to contribute to the advances in P. caribaea var. hondurensis breeding cycles. The purpose of this work was to verify the competition effect on the estimates of genetic parameter and gain of a P. caribaea var. hondurensis progeny trial for wood and resin production as well as to verify the correlation between these traits. The experiment was established in lattice design 10 x 10 (triple), 100 treatments (96 progeny of a clonal seed orchard and four commercial control of P. caribaea var. hondurensis), 10 plants by plot, spaced at 3 m x 3 m. At twelve years after planting the test plots was thinning which left six plants per plot. The total height, diameter at breast height and the resin production o fall remaining were measured at 27 years following the planting. Analysis of deviance, genetic parameter estimates, the expected gain in the selection, with and without competition effect, and genetic and phenotypic correlation was based on REML/BLUP procedure. Significant phenotypic differences were observed among and within progeny for all available traits, especially with regards to evaluating the competition effect. The thinning at 12 years after planting contributed positively to the increase of plant diameter at breast height and resin production, with an average of 30.62cm and 4.83kg/tree .-1 /year -1 . The individual narrow sense of heritability ranged from 0.25 to 0.38 for dbh and volume. The correlations between the growing traits were positive and significant. Therefore, different selection methods will be proposed separately for two traits (resin and wood). Despite ...

inus caribea var. hondurensis é a espécie do gênero Pinus mais importante para regiões tropicais. Sua madeira e resina são utilizadas em vários nichos do setor florestal. Porém, a oferta de sementes com qualidade genética é disponibilizada somente por poucas empresas privadas e instituições públicas. Com o objetivo de contribuir para o avanço do programa de melhoramento de Pinus, a proposta do trabalho foi verificar o efeito de competição sobre as estimativas dos parâmetros e do ganho genético de um teste de progênies de P. caribaea var. hondurensis para produção de madeira e resina, bem como analisar a relação entre esses caracteres. O experimento foi estabelecido em delineamento látice 10 x 10, triplo, com 100 tratamentos (96 progênies de um pomar de sementes clonal de P. caribaea var. hondurensis e quatro testemunhas comerciais), dez plantas por parcelas, no espaçamento de 3 x 3 m. Aos 12 anos após o plantio foi realizado um desbaste seletivo, com base nos caracteres silviculturais, mantendo-se seis plantas por parcela. Aos 27 anos após o plantio, a altura total, o diâmetro à altura do peito e a produção de resina dos indivíduos remanescentes foram mensurados. Análise de deviance e as estimativas dos parâmetros genéticos, o ganho esperado na seleção foram realizadas com e sem o efeito de competição, de acordo com o procedimento REML/BLUP. Ainda foram estimados, as correlações genéticas e fenotípicas e a divergência genética. Diferenças fenotípicas significativas, principalmente considerando o efeito da covariável, foram observadas entre e dentro de progênies para todos caracteres avaliados. O desbaste realizado aos 12 anos após o plantio influenciou de modo positivo os caracteres diâmetro à altura do peito e produção de resina. Os valores médios desses caracteres foram de 30,62 cm e 4,83 kg/arv .- 1 /ano -1, respectivamente. Os coeficientes de...
Keywords: Genetica vegetal; Genetica florestal; Plantas; Melhoramento genetico; Variação (Biologia); Plant-breeding